Effects of Negative Affectivity and Odor Valence on Chemosensory and Symptom Perception and Perceived Ability to Focus on a Cognitive Task. (March 2017) - Nordin, Steven; Aldrin, Lina; Claeson, Anna-Sara; Andersson, Linus
The aim was to gain understanding for the impact of negative affectivity (NA) and odor valance on perceptual aspects during low-level odorous exposure. Fifty-five young adults who were either relatively low or high in NA (anxiety, depression, and somatization) were randomized for exposure to either limonene (pleasant odor) or pyridine (unpleasant odor). In an exposure chamber, they took part in baseline, blank and stable exposure sessions, during which they rated odor intensity, impact on ability to focus on an imagined cognitive task, and intensity of symptoms. The results showed higher ratings of negative impact on ability to focus during exposure to the unpleasant odor compared with the pleasant odor, and an association between NA and symptom intensity, with 18% of the variance in symptom intensity explained by somatization. The association between NA and symptom intensity was found to be driven by the factor sex. These results imply (a) that prior findings of odorous exposure that interfere negatively with work performance may be due to impact of an unpleasant odor on ability to focus on cognitive tasks and (b) that there are associations between NA, sex, and symptoms that may partly be referred to attentiveness to and interpretation of bodily sensations.